Timber business in West Africa: a review and outlook. (1st June 2022) - Uzu, J.; Bettinger, P.; Siry, J.; Mei, B.
Forestry activities are important to the economies of West African nations. This paper aims to assess the current state of forest business in the sub-region, identify factors that may limit the development of the sector and suggest possible solutions. To achieve these objectives, we examined relevant literature and forest statistics from peer-reviewed journals, government publications, and reports from development agencies. Seven West African countries were purposively selected for this study. The results showed that the subregion's forest product trade involves mostly unprocessed logs sourced from natural forests, with plantation forests constituting only 0.35%–3.7% of the focus countries' forest areas. Also, the results from our statistical models showed that GDP per capita had a significant effect on wood production in the focus countries whereas the economic freedom score had no significant effect. The fixed effects revealed that if Nigeria and Ghana had the same GDP per capita as the other focus countries, their wood production would be higher than the other countries. We argue that wood production is likely to increase as the living standards in these countries improve, possibly from increased local demand. However, the lack of robust financial and economic models backing up sound forest management in these countries might discourage new private forest investments.